Pengaruh Penguasaan Tata Bahasa dan Kosakata Terhadap Kemampuan Menulis Teks Naratif Bahasa Inggris: Survei Pada SMK Swasta di Kota Tangerang - Silalahi, Aliong (KALAO'S MARITIME JOURNAL, 2023)
The purpose of this study was to determine the effect of grammar mastery on the ability to write English narrative text. To determine the effect of vocabulary mastery on the ability to write English narrative text and to determine the effect of grammar and vocabulary mastery together on the ability to write English narrative text. The research method used is the survey method. A sample of 77 students was randomly selected from all private vocational high school students in Tangerang city. Data collection is done by conducting a test directly to the sample. Data analysis counduct with descriptive statistical methods, multiple linear regression analysis, statistical test with t- test and F- test. The results of the study showed: 1) There was a significant effect of mastery of grammar and mastery of vocabulary together on the ability to write English narrative text for students of private vocational schools in Tangerang city. This is evidenced by the acquisition of sig = 0.000 <0,05 and Fcount = 97,223. 2) There was a significant effect of grammar mastery on the ability to write English narrative text for students of private vocational schools in Tangerang city. This is evidenced by the acquisition of sig = 0,000 <0,05 and t-count = 4,788. Partially grammar mastery gave a contribution of 19% to the variable of the ability to write English narrative text for students of private vocational schools in Tangerang city. 3) There was a significant effect of vocabulary mastery on the ability to write English narrative text for students of private vocational schools in Tangerang city. This is evidenced by the value of sig = 0.000 <0,05 and tcount = 5,206. Partially (owned) vocabulary mastery contributed 22,5% to the variable of the ability to write English narrative text.